IL-6, D-DIMER AND HIGH-SENSITIVITY C-REACTIVE PROTEIN IN HIV INFECTION - PRELIMINARY STUDY - Ivaylo Pakov; Adelaida Ruseva; Irena Gencheva; Tsetsa Doichinova; Milena Karcheva; Kalina Terzieva; Lyudmila Pakova; Biserka Vasileva; Galya Gancheva (Peytchinski Publishing, 2023)
Combined antiretroviral therapy (cART) provides HIV-infected people life expectancy comparable with HIV-uninfected people and turns the disease into a manageable chronic condition necessitating the need for innovative inflammatory markers. Our purpose was to determine the correlation between IL-6, D-dimer and high-sensitivity C-reactive protein (hsCRP) levels among HIV-infected and the presence of chronic inflammation during general and immunological aging and drug exposure. Material and methods: Comparative prospective study was conducted at 37 HIV-positive persons from the Center for Monitoring and Treatment of HIV-positive Patients at the Clinic for Infectious Diseases, UMBAL "Dr. G. Stranski" - Pleven (target group) and 18 HIV-negative individuals from outpatient practice (control group), aged ≥18 years. Results: The median age of seropositive persons was 40 years (24÷70 years), of the control group - 51 years (29÷72 years); 78% of the target group and 61% of the controls are men. The average duration of ART is 4 years (1÷9 years). The study of specified biomarkers in the target group found increased IL-6 in 8.11% of patients (mean 3.67±1.86 pg/mL; range 1.5÷8.62; 95% CI 3.11-5.02), increased D-dimer in 8.11% (mean 0.37±0.28 µg/mL; 0.21÷1.96; 95% CI 0.3691-0.37459) and increased hsCRP in 10.81% (mean 2.10±1.99 µg/mL; 0.19÷7.0; 95% CI 1.89-2.31). In the control group IL-6 was not increased (mean 2.75±1.67 pg/mL; 1.5÷6.91), D-dimer was increased in 16.67% (mean 0.37±0.17 µg/mL; 0.09÷0.8) and increased hsCRP - in 5.56% (mean 1.76±1.75 µg/mL; 0.19÷5.66). Il-6 was significantly higher in the target group. Conclusion: The implementation of sensitive biomarkers is crucial in the general diagnostic-therapeutic approach in aging with HIV.